IDENTIFICATION AND QUANTIFICATION OF PHYTOCOMPOUNDS IN ACALYPHA INDICA LEAVES - PONNIAH SENTHIL MURUGAN,; GOVINDAN SADASIVAM SELVAM, (International Journal of Pharma and Bio Sciences, 2015)
Acalypha indica, a known medicinal plant in the treatment of various degenerative diseases and a potential source of valuable bioactives. The present study investigates the total phenolic and flavonoid content and also screen for phytocompounds in A. indica leaf extract obtained by two extraction methods, comparatively. Results indicated that the maceration extraction method (MEM) had highest total phenolic content and the sequential extraction method (SEM) showed highest total flavonoid content in methanolic extracts. RP-HPLC (Reversed Phase-HPLC) analysis revealed the presence of gallic acid, caffeic acid, 3,3´-Methylene-bis(4-hydroxycoumarin), syringic acid, ferulic acid, rutin and naringenin in methanolic extract. Major phenolic acid and flavonoid identified were gallic acid (119.7 mg kg-1 dry weight of extract) and naringenin (125.29 mg kg-1) in A. indica extract, respectively. Thus, the results suggest that these identified phenolic compounds makes A. indica a good source of bioactive phenolic compounds and provide desirable health benefits beyond basic nutrition.